A precast beam-column connection using metallic damper as connector: Experiment and application. (June 2021) - Li, Dingbin; Wu, Congxiao; Zhou, Yun; Luo, Weili; Lie, Wenchen
Abstract: The beam-column connection is the most vulnerable part of the precast moment-resisting frame in earthquakes. A novel beam-column connection using a metallic damper is proposed in this paper. Two metallic dampers (a dog-bone (DB) damper and a double-flange (DF) damper) and a suitable connection configuration using channel steel and a U-shaped anchoring unit were introduced. The failure mechanism and mechanical performance of the two dampers were elaborately investigated by a quasi-static test. Test results showed that the flexural strength (81.22 kN·m) and deformation capacity (119.6 mm) of damper DF were better than these of damper DB (64.82 kN·m and 71.8 mm). The cumulative energy absorbed by damper DF was 50.44 kN·m, increasing 69.43% compared with damper DB (29.77 kN·m). The dampers DB and DF were then applied to two proposed connections (PCF-DB and PCF-DF), and a laboratory test was conducted. Test results indicate that the proposed connection was easy to be assembled and disassembled. The plastic damage of the beam-column connections was concentrated in the metallic damper. The connection configuration remained in elastic state. Both in the laboratory tests on damper and proposed connection, the failure pattern of DB was the out-of-plane flexural-torsional buckling while that of DF is the in-plane bending. Graphical abstract: Unlabelled Image Highlights: The beam-column connection is the most vulnerable part of the precast moment-resisting frame in earthquakes. A novel precast beam-column connection using metallic damper as connector was proposed. Two suitable metallic dampers and a connection configuration were introduced. The two metallic dampers were tested and applied to the precast connection.